انتقال الملكية العقاريــة عن طريق عقد الهبـــة في التـــشريعالجــــزائري - فوحمة, ايمان (جامعة الوادي university el-oued, 2016)
تعرض هذه المذكرة بالدراسة لموضوع انتقال الملكية العقارية عن طريق عقد الهبة في التشريع الجزائري. فالعقار وانتقال ملكيته من أهم المواضيع القانونية, تبعا لمكانة العقار نفسه, إذ أن طريقة استغلال هذا الأخير و تدواله لها أهمية حيوية في مجال التنمية الاقتصادية أو الاجتماعية, لما تجنبه خزينة الدولة بمناسبة معاملات الأفراد في عقاراتهم من خلال الضريبة المفروضة على هذه المعاملات,لأجل ذلك تعمدت معظم تشريعات الدول إلى إيجاد آليات وأدوات قانونية تحقق الاستقرار اللازم للملكية العقارية وأهمية هذه الأخيرة ,لأن استقرار الملكية العقارية من أنجع الوسائل الاستثمار الأجنبي لداخل البلاد. لذا نجد المشرع الجزائري في هذا المجال أوجب تضافر وتكامل مجموعة من المراحل التي تنص عن كيفية انتقال ملكية العقار, وذلك حفاظا على المراكز القانونية وتعزيز الائتمان. وبما أن دراسة هذا الموضوع انصبت على عقد الهبة في العقار نجد المشرع فرض في هذا العقد أو التصرف, أركان عامة تتمثل, في التراضي و المحل والسبب.إضافة إلى الأركان العامة السالفة الذكر فرض المشرع الجزائري أيضا أركان خاصة وهي الحيازة والشكلية التي نصت عليه المادة 206 من قانون الأسرة الجزائري. وبما أن الدراسة محصورة عل العقار فقط نجد أن هذا الأخير شكليته تكمن في إفراغه ضمن قالب رسمي أمام موثق, وكذا فرض تسجيله لدى مصلحة التسجيل و أخيرا شهر هذا التصرف لدى المحافظة العقارية حتى يتم الانتقال العقاري, لأن الشهر هو الناقل للأثر العيني. وأخيرا إذا انتقل الشيء الموهوب إلى يد الموهوب له,لا يجوز للواهب الرجوع أو العدول عن هذا التصرف إلا في حالة واحدة حددها المشرع في نص المادة 211 قانون أسرة جزائري وهي حالة الهبة بين الأب والابن وذلك إن لم يتحقق مانع من موانع الأهلية المنصوص عنها في المادة السالفة الذكر . This note provides the study of the subject real property transfer by holding a giveaway in the Algerian legislation Valakar and transfer ownership of the most important legal topics, depending on the status of the drug itself, since the exploitation of the latter and Tdoualh of vital importance in the field of economic development or social way, because of the state treasury to avoid the occasion of the individual transactions in their property through a tax on these transactions, to order it most of the legislation of States deliberately to create legal tools necessary to verify the ownership of real estate stabilization mechanisms and the importance of the latter, because the stability of the real property of the most effective means of foreign investment into the country So we find the Algerian legislator in this area enjoined combination and integration of a series of stages, which states how the ownership of the property transfer, and to protect their legal centers and credit enhancement. As the study of this topic focused on holding the gift of the property we find the legislature to impose in this contract or disposition, General Staff of is, in compromise and the shop and Sbb.adhavh to the General Staff of the aforementioned imposition of Algerian legislature also the pillars of a private a possession and formalities provided for in Article 206 Algerian family law. within a formal template front documented, as well as the imposition of registration with the registration interest and finally a month this practice before the real estate to maintain until the transition real estate, because the month is the carrier of the impact of in-kind. Finally, if the talented thing go to the hands of the donee, not the donor may return or reverse this act, except in one case identified by the legislator in the text of Article 211 Algerian family law, a gift case between the father and son so that the mind does not come from the civil contraindications provided for in Article above.
مدكرة ماستر